C1q is elevated during chronic Staphylococcus epidermidis central nervous system catheter infection - Beaver, Matthew; Bergdolt, Lara; Dunaevsky, Anna; Kielian, Tammy; Skar, Gwenn L. (Frontiers in Immunology, 2024)
Significant neurologic morbidity is caused by pediatric cerebrospinal fluid (CSF) shunt infections. The underlying mechanisms leading to impaired school performance and increased risk of seizures are unknown, however, a better understanding of these mechanisms may allow us to temper their consequences. Recent evidence has demonstrated important roles for complement proteins in neurodevelopment and neuroinflammation. We examined complement activation throughout Staphylococcus epidermidis (S. epidermidis) central nervous system (CNS) catheter infection. In addition, based on accumulating evidence that C3 plays a role in synaptic pruning in other neuroinflammatory states we determined if C3 and downstream C5 led to alterations in synaptic protein levels. Using our murine model of S. epidermidis catheter infection we quantified levels of the complement components C1q, Factor B, MASP2, C3, and C5 over the course of infection along with bacterial burdens. We found that MASP2 predominated early in catheter infection, but that Factor B was elevated at intermediate time points. Unexpectedly C1q was elevated at late timepoints when bacterial burdens were low or undetectable. Based on these findings and the wealth of information regarding the emerging roles of C1q in the CNS, this suggests functions beyond pathogen elimination during S.epidermidis CNS catheter infection. To identify if C3 impacted synaptic protein levels we performed synaptosome isolation and quantified levels of VGLUT1 and PSD95 as well as pre-, post-and total synaptic puncta in cortical layer V of C3 knockout (KO) and wild type mice. We also used C5 KO and wild type mice to determine if there was any difference in pre-, post-and total synaptic puncta. Neither C3 nor C5 impacted synaptic protein abundance. These findings suggest that chronic elevations in C1q in the brain that persist once CNS catheter infection has resolved may be modulating disease sequalae.